STRATEGIC ENVIRONMENTAL ASSESSMENT (SEA) OF MULTIMODAL TRANSPORT ON NH-9 IN HYDERABAD CITY USING REMOTE SENSING AND GIS (International Journal of Engineering and Computer Science, 2017)
The paper describes the work of the Strategic Environmental Assessment on the National Highway No- 9 connecting Hyderabad and Pune junction which has been deliberately worked and surveyed in the recent past as multi modal transport corridor to construct the elevated Metro rails in near future.The study purpose is to provide a multi - modal land- use and transport designed to lead to a preferred environmental and development strategy corridor. The study was intended to be strategic, both in its identification of options and in its assessment of impacts. It is to look forward over a 25 year planning period, and the focus was to be on quick movements, comfortable and environment friendly traffic. The paper briefly describes the present results in terms of impacts on travel, land- use and the environment.While the study successfully demonstrated a methodology for strategic environmental assessment, further, work on the land- use and transport strategy is required before firm conclusions can be drawn and the broad outline strategy can be converted into specific policies or plans. The key appraisal framework tools for the study are,a)      The Transport model andb)       The Land- use model.GIS has played a vital role in the study of Transport and the Land use Models for determining the Strategic Environmental Assessment for any long term project .It is one of the fastest growing technologies of present time. It has emerged as powerful and sophisticated means to manage vast amounts of geographic data. This paper also enhances the key roles played by GIS and Remote Sensing in various application maps and understanding of the Environmental issues with respect to the corridors